Pengaruh Variasi Fraksi Volume Biokomposit Batang Padi dan Resin Epoxy-Polyester Terhadap Kekuatan Bending dan Daya Serap Air - Ghifari, Abizar; Kencanawati, Cok Istri Putri Kusuma; Lokantara, I Putu; Suarsana, I Kt (Teknik Desain Mekanika, 2024)
Abstract Each year, the production of rice straws in Indonesia increases, it is reported that the production reaches 54,42 in 2021. This results in massive waste products in approximately 62% straws were burned and the rest is utilized for livestock feeding. Hence, rice straws are put for consideration to be analyzed in this research. This paper uses the mix of epoxy-polyester resin with the ratio of 9:1, combined with hardener on 2:1 ratio as a matrix. The combination of rice straw fibers and resin in fraction of volume, consists of fibers 5% ; resin 95%, fibers 10% ; resin 90% resin and 15% fibers ; 85% resin. The speciments are moulded using acrylic mold with hand lay-up technique. The size of the speciments are decided upon the ASTM D790-03 for Bending Test and ASTM D570-98 for Water Absorption Test, and Photo Micro Test to support other related assessments. According to the results of this study, the highest bending stress was found in 5% fraction of fiber with 47,352 MPa. In contrast, the lowest stress was found in 15% fraction of fiber with 21,463 MPa. Meanwhile, the highest strain was found in 15% fraction of fiber with 6,064 and the lowest was in 5% fraction of fiber with 4,320. As for the elastic modulus, the highest result was in 5% fraction of fiber with 1,077 GPa and the lowesr was in 15% fraction of fiber with 0,408 Gpa. In which this result was supported by the photo micro result. The result shows a bond between fiber and matrix that is present in the composite. According to the water absorption test, the highest absorption ability was found in 15% fraction of fibers with the amount of 3,28% and the lowest was found in 5% fraction of fibers with the amount of 2,54%. All mentioned above concludes that the water absorption ability on 5% fraction of fibers was the highest. This may be due to the effect of fibers on water absorption ability of the speciments. Keywords: Rice Straw, Epoxy Resins, Polyester Resins, Mix of Epoxy-Polyester Resins, Volume Fraction, Bending Test, Water Absorption Test, Photo Micro